UNRAVELING CULTURAL COMPLEXITY IN DIGITAL TRANSLATION: AN EXPLORATION OF CULTURAL TRANSLATION - Jepri (Prologue: Journal on Language and Literature, 2024)
The interconnectedness of the contemporary world necessitates the crucial role of digital translation in bridging communication gaps across linguistic and cultural divides. However, this process is fraught with challenges, particularly the intricate nuances of cultural differences. This article embarks on an investigation of cultural translation within the digital age. The article delves into the multifaceted nature of cultural gaps and their impact on digital translation practices. Through a qualitative descriptive methodology, the article examines the intricacies of cultural nuances with the aim of 1) Complexity of cultural nuances in translation, 2) The Limitations of Machine Translation for Cultural Understanding, 3) Importance of human expertise in translation, 4) Strategies for enhancing cultural sensitivity in translation and 5) Interdisciplinary insights into cultural translation. By illuminating the complexities of cultural translation and providing guidance, this article endeavours to contribute to the advancement of digital translation practices on a global scale. This is achieved through the application of Cultural Translation theory, drawing upon findings in the areas of 1) Complexity of cultural translation, 2) Challenges using machine translation 3) Human expertise in translation, 4) Strategies for cultural sensitivity in translation and 5) Interdisciplinary insights of cultural translation